Solvent-driven micro/nanostructures of squaraine and croconaine dyes based on quinoxalinone for visual detection of nerve agent simulants. (December 2022) - Zhang, Shouxin; Zhou, Chuan; Zhang, Min; Zhao, Yue; Yuan, Bo; Yang, Bo; Li, Heguo
Abstract: The detection of nerve agents has been the focus of research due to their extreme threat for human health and safety. In this paper, the quinoxalinone-based squaraine (NESQ ) and croconaine (NECR ) dyes are synthesized and used as chemosensors to investigate the sensing properties with diethyl chlorophosphate (DCP) in solvents. They exhibit a huge absorption spectra red-shift from visible region to near-infrared region due to the transformation of anionic basic form and zwitterionic acidic form, which is verified by experiments and theoretical calculations. The self-assembly micro/nanostructures transformation of NESQ and NECR can be driven by adding different solvents, which is characterized by SEM and AFM technology. Upon adding DCP, the absorption wavelength of NESQ and NECR in DMF respectively exhibits 186 nm and 281 nm red-shifts from visible region to near-infrared region with obvious color change, which is larger than the previously reported. The proposed sensing mechnism was verified by 1 H NMR spectra and SEM technology. Compared to NECR, NESQ exhibits a lower limit of detection and a faster responsive time for sensing DCP. The characteristics of these dyes would provide a new design strategy of chromogenic chemsensors with large wavelength shift and self-assembly morphologies transformation for the visual detection of nerve agents. Graphical abstract: Image 1 Highlights: The dyes exhibit a large absorption spectra change in different solvent. The self-assembly micro/nanostructures can be transformed by solvent driven. A huge red-shift is observed in DMF after adding diethylchlorophosphate. They show a good sensitivity and fast response time with diethyl chlorophosphate.